Solvent fractionation of rice bran oil to produce a spreadable rice bran product. Issue 8 (10th July 2013) - Bakota, Erica L.; Winkler‐Moser, Jill K.; Hwang, Hong‐Sik; Bowman, Michael J.; Palmquist, Debra E.; Liu, Sean X.
Abstract Rice bran oil is becoming increasingly popular as a functional ingredient, due to its high stability and health benefits. We detail here a new solvent fractionation procedure for the production of a spreadable product derived from rice bran oil. Four different experimental conditions for fractionation yielded four statistically distinct populations. The spreads show distinctive trends in their physical properties, thermal behavior, and rheology, based on incubation time. The rice bran oil based spreads produced in this work consist primarily of rice bran oil but also contain rice bran wax, tocopherols, tocotrienols, and γ‐oryzanol, as well as other sterols. Relative to rice bran oil, they are enriched in rice bran wax, saturated fatty acids, and sterols, all of which contribute to a more rigid rheological profile than that of rice bran oil. This solvent fractionation process may be used to develop rice bran oil based spreads as functional ingredients or products that may replace nut butters. Practical applications: A need exists for structured lipids and spreadable products that are shelf stable, resistant to oxidation, allergen‐free, and provide health benefits to consumers. The fractionation procedure described here may be used to acquire a spreadable rice bran product from crude rice bran oil. This product is novel in composition in that it contains a significant proportion of rice bran wax, as well as tocopherols, tocotrienols, phytosterols, and γ‐oryzanol. γ‐Oryzanol has been shown to reduce cholesterol and has also been shown to have antioxidant activity. This spreadable product is also free of allergens present in many nut‐based spreads and thus may be used as a functional ingredient in the development of a host of allergen‐free products.